Changes in the spatial structure of services and their implications for the labour market of the Silesian Province - Kłosowski, Franciszek (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2015)
The aim of the analysis is to determine the changes occurring in the services of the Silesian Voivodeship with special regard to the period after the year 2008(economic crisis). The collected material enabled the authors to formulate the following conclusions: First of all, the analysis of the statistical data as well as the results of poll research allows the authors to state that there are hardly any reasons to speak of economic crisis with regard to the services provided within the area of the Silesian Voivodeship. Despite the fact that the rate of development was considerably decreased in the area, it still occurred at a delay in comparison to the global crisis (the years 2010 and 2011). Secondly, the investigated period of time revealed considerable changes in the level of service development with regard to municipalities of the Silesian Voivodeship. Little though did it affect the general image of service development, which was still dominated by Katowice. There was, however, a small decrease in spatial disproportions within the level of service development. Thirdly, the increase of employment in services reduced the negative consequences for the labour market. The high level of service development was considered to favourably affect the unemployment rate, although there is no significant statistical relationship between changes in services and similar changes in unemployment level.